The Role of Students in Strengthening Digital Literacy in Islamic Boarding School Environments - Hidayatullah, Subhan; Febyola N, Rima; Lestari, Heny; Analisa, Analisa; Fadil, Ihsan; Yahya, Muhammad Alfarabi; Maulina, Nurcahyati; Maulana, Agus; Pratiwi, Amanda Gadis; Lubis, Riza Ardhiansyah (Communautaire: Journal of Community Service, 2025)
Improving digital literacy remains a significant challenge in s (Islamic boarding school), particularly amidst the rapid pace of digital transformation. Students, as key agents of change, play a strategic role in introducing and strengthening digital competencies within these traditional educational environments. Community service initiatives carried out at s aim to increase digital awareness through structured training on the wise and productive use of technology. The program employed a three-phase approach: observation, hands-on workshops, and continuous evaluation. The findings reveal increased student understanding of digital ethics, cyber safety, and the use of digital tools such as Canva for educational content creation. Moreover, the initiative fostered a more collaborative and inclusive digital learning culture. However, challenges such as limited technological infrastructure and constrained training time were identified. It is recommended that future programs incorporate extended mentoring periods and provide infrastructure support to sustain digital literacy development. This initiative offers a replicable model for empowering digital literacy in Islamic boarding school settings and highlights the potential of university-student partnerships in bridging the digital divide within religious educational institutions.